2017
DOI: 10.2146/ajhp150797
|View full text |Cite
|
Sign up to set email alerts
|

Developing and improving residency research training

Abstract: A review of the literature identified three strategies that can enhance residency research training: formalizing the process, engaging expertise and collaboration, and formatting the training for use across all pharmacy residency programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 36 publications
0
30
0
1
Order By: Relevance
“…offer a wide variety of research and scholarship training opportunities. 7,8 Additionally, substantial variability in the quality and depth of research experiences for trainees and high rates of attrition before completing the research experience have been demonstrated within Pharm.D. programs.…”
Section: Schools Of Pharmacy and Pharmacy Residency Training Programsmentioning
confidence: 99%
“…offer a wide variety of research and scholarship training opportunities. 7,8 Additionally, substantial variability in the quality and depth of research experiences for trainees and high rates of attrition before completing the research experience have been demonstrated within Pharm.D. programs.…”
Section: Schools Of Pharmacy and Pharmacy Residency Training Programsmentioning
confidence: 99%
“…3 Despite this promoted ideal, most ACGME programs provide limited opportunities for residents to participate in IP QI teams. [12][13][14][15][16][17] While numerous QI curricula for internal medicine (IM) residents, 10,[18][19][20][21][22][23][24][25][26][27][28] graduate nursing students, [29][30][31][32][33] and other health professional trainees [34][35][36] have been published, we identified only one longitudinal, project-based curriculum for IP trainees in a primary care setting. 37 Comparable to the IP QI curriculum depicted by Hunt and colleagues, we created an experiential QI curriculum for primary care trainees that drew on best practices from professionspecific QI curricula, 1,12,18,21,[37][38][39][40][41][42][43][44][45][46][47] and our experiences as QI and IP educators.…”
Section: Introductionmentioning
confidence: 99%
“…The Accreditation Council for Graduate Medical Education (ACGME) Clinical Learning Environment Review program noted that “IP, team-based quality improvement efforts… provide residents… with experiential learning that goes beyond basic QI methods to include developing skills and behaviors in shared leadership, communications, systems-based thinking, change management, and professionalism.” 3 Despite this promoted ideal, most ACGME programs provide limited opportunities for residents to participate in IP QI teams. 12 – 17 While numerous QI curricula for internal medicine (IM) residents, 10 , 18 28 graduate nursing students, 29 33 and other health professional trainees 34 36 have been published, we identified only one longitudinal, project-based curriculum for IP trainees in a primary care setting. 37 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, primary project management experience is required by the American Society of Health‐System Pharmacists (ASHP) for residencies; however, this currently may be accomplished through completion of a quality improvement project rather than a research project 5 . Several efforts have been made to improve the outputs of residency research and scholarship by approaching team‐based research to improve experiences for residents 6,7 . While there is high heterogeneity of resident research development, a formalized training approach is essential for research skills development and can improve scholarly output from resident research projects 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Several efforts have been made to improve the outputs of residency research and scholarship by approaching team‐based research to improve experiences for residents 6,7 . While there is high heterogeneity of resident research development, a formalized training approach is essential for research skills development and can improve scholarly output from resident research projects 6,7 . Though the required project management experience may encourage some residents to contribute to the medical literature throughout their careers, this training is often inadequate by itself.…”
Section: Introductionmentioning
confidence: 99%